Resilient agri-food systems for nutrition amidst COVID-19: evidence and lessons from food-based approaches to overcome micronutrient deficiency and rebuild livelihoods after crises - Heck, S.; Campos, Hugo; Barker, I.; Okello, J.J.; Baral, Arun; Boy, Erick; Brown, Lynn; Birol, Ekin (Springer, 2020)
COVID-19 has had an instant effect on food systems in developing countries. Restrictions to the movement of people and goods have impaired access to markets, services and food. Unlike other concurrent crises, rather than threatening the material hardware of food systems, COVID-19 has so far affected the ‘software’ of food systems, highlighting again that connectivity is at the heart of these systems. Drops in demand, the loss of markets and employment and growing concerns about international cooperation are indications of possible deeper disruptions to come. Amidst this uncertainty, strategies to safeguard food and nutrition security of the world’s poor need to prioritize diversification of production and markets. Nutritious, biofortified crops such as potato, sweetpotato, but also wheat, maize and beans among others, can play a more significant role to provide key micronutrients (vitamin A, iron, zinc) at large scale. Strong local market chains, robust smallholder production systems and increasing commercial utilization make these crops powerful vehicles for securing nutrition when markets and mobility look uncertain. We posit that the evolving impacts of COVID-19 provide an opportunity to focus agricultural innovations, including the development and delivery of biofortified crops, on new and more specifically defined ‘jobs to be done’ throughout the food system. This will help bridge some of the current disruptions in supply and demand and will help prepare food systems for future crises.